2007
DOI: 10.1016/j.schres.2006.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to Tardive Dyskinesia in chronic schizophrenia subjects: Role of oxidative stress pathway genes

Abstract: Keywordsnorth India; Tardive Dyskinesia; oxidative stress; NOS3; NQO1; Single nucleotide polymorphisms; association Tardive Dyskinesia (TD) is a severe debilitating movement disorder with a potentially irreversible course developing in schizophrenia patients under long term treatment with classical neuroleptics. Its development in a subset of patients (~20-25%), familial nature, and concordance amongst twins indicate a possible genetic basis (for review see Muller et al. 2004). In addition to the classical dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…None of the SNPs tested were associated with the development of TD. However, they did find an association between the NOS3 variant and severity of TD (Thelma et al, 2007). Therefore, the relationships between ROS-related genes and TD remain controversial.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…None of the SNPs tested were associated with the development of TD. However, they did find an association between the NOS3 variant and severity of TD (Thelma et al, 2007). Therefore, the relationships between ROS-related genes and TD remain controversial.…”
Section: Discussionmentioning
confidence: 96%
“…A recently developed novel brain-targeted antioxidant, N-acetyl cysteine amide, has been reported to reduce haloperidol-induced vacuous chewing movements in rats (Sadan et al, 2005). Most recently, Thelma et al (2007) performed a genetic association study of several variants of oxidative stress-related genes (SOD2, UCP2, NOS1, NOS1, NOS3, GST-M1, GST-T1, GST-P1, and NQO1) and the development of TD in Indian patients with schizophrenia. None of the SNPs tested were associated with the development of TD.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GCLM codes for the first rate-limiting enzyme in glutathione synthesis and its decreased expression in SZ patient fibroblasts (Tosic et al, 2006) and in peripheral blood of SZ patients (Che et al, 2009) has been reported. A number of studies have reported that oxidative stress is involved in the pathophysiology of TD (Thelma et al, 2007), providing a testable mechanism underpinning the genetic association. MTHFR , a commonly investigated candidate gene in SZ is essential for the conversion of homocysteine to methionine.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have identified DRD3, DRD2, MnSOD, CYP2D6, CYP1A2, HTR2A to be reproducibly associated with TD, 39,[55][56][57][58][59] although studies in other genes, such as HTR2C, NQO1 and GABRB2, require further investigation. [60][61][62] As nearly all antipsychotics target more than one receptor, it is more likely that TD is not related to one receptor gene, but instead represents a polygenic condition with each gene contributing a small proportion of the risk to this disorder. Gene-gene interaction studies may help to identify and clarify pathways that contribute to TD.…”
Section: Discussionmentioning
confidence: 99%